A High Serum Phosphate and Calcium-Phosphate Product Is Associated With Cerebral Small Vascular Disease in Patients With Stroke: A Real-World Study - Lv, Wenjing; Cui, Can; Wang, Zixuan; Jiang, Junqi; Deng, Binbin (Frontiers in Nutrition, 2022)
Cerebral small vessel disease (CSVD) is a slowly progressive disease, often accompanied by stroke, and results in dementia, depression, and cognitive impairment. It was already known that calcium and phosphorus metabolism (CPM) disorders were associated with vascular-related adverse events. The risk factors of CSVD and the relationship between serum calcium (Ca), phosphorus (P), calcium-phosphate product (Ca × P), and CSVD in patients with stroke without CPM disorders are still obscure. In our study, 528 patients with stroke without CPM disorders were enrolled in a cohort from a consecutive hospital-based stroke registry, with 488 patients with CSVD as cases and 140 without CSVD as controls. The patients with CSVD were further sub-grouped into lacunes, white matter hyperintensities (WMHs), and cerebral microbleeds (CMBs). By applying univariate and multivariate logistic regression analysis, the following novel findings were obtained: (i) up to 76.19% of patients with stroke had signs of CSVD, and lacunes are the most common subtype. Notably, 22.96% of patients with CSVD had multiple subtypes coexisted. (ii) Compared with patients without CSVD, patients with CSVD had higher levels of age, rate of hypertension or diabetes, serum Ca, P, Ca × P, and lower levels of white blood cell (WBC) and hemoglobin (HB). (iii) We developed 2 predictive models and nomograms for predicting CSVD, in addition to the known factors (age and hypertension). The levels of P and Ca × P were positively correlated with the risk of CSVD (P: OR = 3,720.401, 95% CI (646.665–21,404.249); Ca × P: OR = 1.294, 95% CI (1.222–1.370)). (iv) The models were further validated in subtypes of CSVD, including lacunes, WMHs, and CMBs, and the results were still valid among the subtypes. In summary, CSVD was highly prevalent in patients with stroke, and high serum P and Ca × P are potential risk factors of CSVD and all subtypes including lacunes, WMHs, and CMBs.